Rethinking the drivers of coronavirus virulence and pathogenesis; toward an understanding of the dynamic world of mutations, indels, and recombination within the alphacoronaviruses - Ximena A. Olarte-Castillo; Laura E. Frazier; Jessica C. Gomes Noll; Annette Choi; Gary R. Whittaker (mBio, 2025)
ABSTRACT Alphacoronaviruses are widespread but understudied in comparison to betacoronaviruses. Within the alphacoronaviruses is the species Alphacoronavirus-1, which comprises distinct viruses of cats, dogs, and pigs, along with a separate species that infects mustelids—as well as other related viruses of pigs and circulating human viruses. High-pathogenicity feline coronavirus (FCoV) is infamous as the cause of feline infectious peritonitis (FIP), existing as two distinct genotypes (types 1 and 2) and transmitted as a low-pathogenicity virus. The high-pathogenicity variants arise in cats infected with FCoV, and while the mutations responsible remain enigmatic, the main determinant is the spike glycoprotein. FCoV-1 disease outcome is driven by a combination of both within- and between-host evolution. Virulence can be largely explained by the “internal mutation hypothesis,” which argues that high-pathogenicity—but poorly transmissible—variants are selected in individual cats. Canine coronaviruses are generally considered low pathogenicity but can cause severe enteritis and can be systemic. Notably, the canine coronavirus spike gene periodically recombines with FCoV-1 to generate FCoV-2, exemplified by FCoV-23, which has caused a widespread outbreak of FIP in Cyprus and has a notably truncated spike N-terminal domain (NTD). In pigs, coronaviruses often cause severe gastrointestinal disease but can become respiratory and have low pathogenicity based on what can also be considered an “internal deletion” of the spike NTD. These viruses may exist as a dynamic “metavirome” (the sum of all viral genomes present in a sample) that is in a constant state of flux, presenting notable challenges for disease surveillance and management.